1998
DOI: 10.1080/1359866980260306
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the Writing of Cases: experiences with preservice Master of Teaching students

Abstract: During the final phase of their first year, preservice students in the Master of Teaching programme at the University of Sydney are required to write their own case stories from experience. This process serves to help them make individual and collective sense of what has occurred in the course of their initial six week practicum, which was preceded by 20 weeks of intensive coursework based on several forms of case methodology. Through a carefully constructed writing workshop, the university teacher writes alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Hunter and Hatton's (1998) study of case story writing based on students' experiences revealed that peer and professor collaboration helped pre-service teachers move from initial writing that demonstrated low levels of reflection to higher levels of thinking. I believe that writing helped these pre-service teachers to develop their thoughts that are evident in how they wrote thoughtful and reflective journal entries.…”
Section: Situating the Contexts Of Reflectionmentioning
confidence: 99%
“…Hunter and Hatton's (1998) study of case story writing based on students' experiences revealed that peer and professor collaboration helped pre-service teachers move from initial writing that demonstrated low levels of reflection to higher levels of thinking. I believe that writing helped these pre-service teachers to develop their thoughts that are evident in how they wrote thoughtful and reflective journal entries.…”
Section: Situating the Contexts Of Reflectionmentioning
confidence: 99%
“…This finding is in line with the related literature as the case-based methods were found to be highly effective in triggering reflection (Celik, et. al., 2012;Hunter & Hatton, 1998;Levin, 1995;Lundeberg & Yadav, 2006;Merseth, 1996;Santagata & Angelici, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers, as claimed by Schön (1983), need to possess practical knowledge situated in the context of time and place. A case story is an appropriate tool to document experiences and generate reflections, because telling and writing stories is linked with facilitating, sharing, reflecting and establishing a social atmosphere within which a collective sense of experiences is established (Hunter & Hatton, 1998). Therefore, the case story method, which involves writing and sharing stories based on observations and experiences, has been recognized as a potential method to be used in teacher education.…”
mentioning
confidence: 99%
“…The feedback on their work, however, was a critical part of the learning. Scholars have pointed to the ways that student collaboration with a faculty member during reflective writing practices can help move them from low levels of reflection to higher order thinking (Hunter & Hatton, 1998;Pedro, 2011, p. 62). Giovanangeli et al (2018) point to the ways that mentoring is essential to teasing out intercultural learning.…”
Section: Adjustments To the Course: Reframing And Gradingmentioning
confidence: 99%